2023
DOI: 10.1177/22799036231208356
|View full text |Cite
|
Sign up to set email alerts
|

The impact of MDQ positivity on quality of life impairment: Does it support the hypothesis of “Dysregulation of Mood, Energy, and Social Rhythms Syndrome” (DYMERS)?

Mauro Giovanni Carta,
Goce Kalcev,
Alessandra Scano
et al.

Abstract: Background: DSM-5 separates bipolar (BD) from depressive disorders, but some experts consider BD as part of a spectrum of mood disorders. The interpretation of numerous false positives of BD screened by the Mood Disorders Questionnaire (MDQ) is part of this debate. Recent study results suggest that the worsening of health-related quality of life (H-Qol) associated with MDQ positivity does not depend solely on mood disorders. This study aims to clarify whether the impairment may be due to other concomitant diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…The dysregulation of biological rhythms is a known trigger for crises in bipolar spectrum disorders [ 20 ]. Moreover, biological rhythms significantly impact individuals’ quality of life (QoL) [ 21 , 22 , 23 ]. Additionally, it has been suggested that the subclinical dysregulation of social and biological rhythms could serve as a common risk factor for various psychiatric disorders, including BD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulation of biological rhythms is a known trigger for crises in bipolar spectrum disorders [ 20 ]. Moreover, biological rhythms significantly impact individuals’ quality of life (QoL) [ 21 , 22 , 23 ]. Additionally, it has been suggested that the subclinical dysregulation of social and biological rhythms could serve as a common risk factor for various psychiatric disorders, including BD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%